Professional Competences of Preschool Teachers: Integrated College-University System - SHAKIROVA, AIGUL MINTAGIROVNA; FAHRUTDINOVA, REZIDA AKHATOVNA; SKOROBOGATOVA, ANNA ILDAROVNA; DIUANOVA, RAIKUL KENESBAYEVNA (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT Recently, the training of specialists from a competency-based approach has been increasingly debated; such competences in current students are presented as a social, personal, behavioral, and integral phenomenon as a result of education. This fact does not represent a requirement for the content of education in terms of pedagogical teaching objectives, outcomes and technologies. In the experimental part of the study, the authors of the work presented a model for the development of professional competences of students based on an integrated college-university system in the context of the implementation of new educational standards. RESUMEN Recientemente, la formación de especialistas desde un enfoque basado en competencias se ha debatido cada vez más; tales competencias se presentan en los estudiantes como un fenómeno social, personal, conductual, e integral como resultado de la educación. Este hecho no representa un requisito para el contenido de la educación en cuanto a objetivos, resultados y tecnologías de enseñanza pedagógica. En la parte experimental del estudio, los autores del trabajo presentaron un modelo para el desarrollo de competencias profesionales de los estudiantes basado en un sistema integrado de universidad-instituto de educación superior en el contexto de la implementación de nuevos estándares educativos.